Disasters, hazards and law - Deflem, Mathieu (Bingley, U.K. : Emerald, 2012)
This volume deals with important social-science issues of law and legal control pertaining to disasters and hazards in a variety of contexts. The orientation of this volume is driven by relevant recent occurrences, such as hurricanes Katrina and Irene in the United States; the 2010 BP oil spill, and the 2011 Japanese earthquake and tsunami. Thematically diverse within the province of the social and behavioral sciences related to law and law-related problems, the chapters in this volume are not restricted in terms of theoretical approach and methodological orientation. Topics addressed include: legal controls pertaining to disaster prevention, response, and mitigation; regulations and policies concerning hazardous conditions; and crime and the control thereof in post-disaster situations.
Introduction : disasters and hazards in socio-legal studies / Mathieu Deflem -- Disaster myth or reality : developing a criminology of disaster / Bethany L. Brown -- 'Not only injurious to individuals, but dangerous to the state' : a theory of disaster crime / Susan S. Kuo -- Disaster, war, and drugs : policy levers and rebuilding communities / Megan Reid ... [et al.] -- Federalism, law, and the ethics of disaster evacuations / Tanya L. Settles -- Policing disasters : the role of police in the pre-disaster planning and post-disaster responses / Sean P. Varano, Joseph A. Schafer -- Transforming oil activism : from legal constraints to evidenciary opportunity / Sabrina McCormick -- Environmental policy for chemical pollution in Taiwan : the An-Shun plant case / Yungnane Yang -- The federal disaster : the failed logic of disaster prevention in New Orleans / Min Hee Go -- New Orleans : post-disaster dual dualism in labor markets and development / Aaron Schneider -- The prison city of New Orleans : law's responses to the disaster of Hurricane Katrina / Alicia J. Ferrara, Peter G. Stillman, Adelaide H. Villmoare -- Perceived risk, criminal victimization, and community integration : mental health in the aftermath of hurricanes Katrina and Rita / Alexander Lu.
Keywords: Social Science -- General; Social Science -- Criminology; Social Science -- Violence in Society; Society & social sciences; Social services & welfare, criminology; Emergency management -- Law and legislation; Disaster relief -- Law and legislation